2008
DOI: 10.1161/atvbaha.107.160085
|View full text |Cite
|
Sign up to set email alerts
|

Far Infrared Therapy Inhibits Vascular Endothelial Inflammation via the Induction of Heme Oxygenase-1

Abstract: Objective-Survival of arteriovenous fistulas (AVFs) in hemodialysis patients is associated with both far infrared (FIR) therapy and length polymorphisms of the heme oxygenase-1 (HO-1) promoter. In this study, we evaluated whether there is an interaction between FIR radiation and HO-1 in regulating vascular inflammation. Methods and Results-Treatment of cultured human umbilical vein endothelial cells (ECs) with FIR radiation stimulated HO-1 protein, mRNA, and promoter activity. HO-1 induction was dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 42 publications
(47 reference statements)
3
115
0
1
Order By: Relevance
“…Human umbilical vein endothelial cells (HUVEC) or human aortic endothelial cells (HAEC) were purchased from Lonza (Allendale, NJ) and serially cultured on gelatin-coated dishes, as we previously described (28). Cells were propagated in M199 medium supplemented with 20% bovine calf serum, 2 mM L-glutamine, 50 g/ml endothelial cell growth factor, 90 g/ml heparin, and 100 U/ml of penicillin and streptomycin in an atmosphere of 95% air-5% CO 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human umbilical vein endothelial cells (HUVEC) or human aortic endothelial cells (HAEC) were purchased from Lonza (Allendale, NJ) and serially cultured on gelatin-coated dishes, as we previously described (28). Cells were propagated in M199 medium supplemented with 20% bovine calf serum, 2 mM L-glutamine, 50 g/ml endothelial cell growth factor, 90 g/ml heparin, and 100 U/ml of penicillin and streptomycin in an atmosphere of 95% air-5% CO 2.…”
Section: Methodsmentioning
confidence: 99%
“…Membranes were prehybridized for 4 h at 68°C in rapid hybridization buffer (Amersham, Arlington Heights, IL) and then incubated overnight at 68°C in hybridization buffer containing [ 32 P]DNA probes (1 ϫ 10 8 cpm) for HO-1, Nrf2, or 18S mRNA. DNA probes were generated by RT-PCR and labeled with [ 32 P]dCTP using a random priming kit (Amersham, Arlington Heights, IL) (28). After hybridization, membranes were washed and exposed to X-ray film at Ϫ70°C, and HO-1 expression was quantified by scanning densitometry and normalized with respect to 18S rRNA.…”
Section: Methodsmentioning
confidence: 99%
“…The nonthermal effects induce eNOS expression, inhibit neointimal hyperplasia, and reduce oxidative stress. In a clinical study in dialysis access, FIR increased access blood flow and unassisted patency through AVFs (59), likely through activation of HO-1 pathways and reduction in endothelial inflammation (60). A recent randomized controlled trial showed that FIR improves the access blood flow, maturation, and long-term patency of newly created AVFs in patients with CKD stages 4 and 5 (61).…”
Section: Far-infrared Therapymentioning
confidence: 99%
“…This treatment involves the application of electromagnetic radiation (wavelengths of 3-25 mm) to the skin surface overlying the vascular access. The electromagnetic radiation, which travels 2-3 cm below the skin surface, is hypothesized to be beneficial for the vasculature by inducing vasodilation, decreasing oxidative stress (82), inhibiting cell proliferation (83), and inducing protective enzymes, such as heme oxygenase-1 (84). The emitting device is positioned approximately 25 cm above the arm for 30-60 minutes per treatment.…”
Section: Perivascular Approachesmentioning
confidence: 99%